2018
DOI: 10.1371/journal.pntd.0006797
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating the efficacy of community-wide use of systemic insecticides in dogs to control zoonotic visceral leishmaniasis: A modelling study in a Brazilian scenario

Abstract: Systemic insecticides in dogs have been suggested as a public health intervention to prevent human cases of Zoonotic Visceral Leishmaniasis (ZVL). But, currently there are no systemic insecticides for dogs registered against zoo-anthropophilic pool blood feeding phlebotomine flies. We predict the impact of community-wide use of systemic insecticide in dog populations as a public health measure to control transmission of Leishmania infantum to humans using a mathematical model. We developed a Susceptible-Expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…gomezi for CL (Figure 6), and an abundance of reservoir mammals for the parasite, 37,75 which aid the pathogen's epidemiological circuit and, therefore, maintain the transmission rates. Regarding mammalian reservoirs, canines are the main reservoirs for the domestic and peri-domestic transmission of VL 76 in Brazil, 77,78 Spain, 79 and other endemic countries. Studies have been conducted to measure the impact of canines on the incidence of VL, and the effectiveness of euthanasia and other control strategies to interrupt transmission.…”
Section: Discussionmentioning
confidence: 99%
“…gomezi for CL (Figure 6), and an abundance of reservoir mammals for the parasite, 37,75 which aid the pathogen's epidemiological circuit and, therefore, maintain the transmission rates. Regarding mammalian reservoirs, canines are the main reservoirs for the domestic and peri-domestic transmission of VL 76 in Brazil, 77,78 Spain, 79 and other endemic countries. Studies have been conducted to measure the impact of canines on the incidence of VL, and the effectiveness of euthanasia and other control strategies to interrupt transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Deceased dogs were replaced by newly introduced dogs, which have a probability of being already infected. The VL transmission model is based on a localised vectorial capacity of the sand fly population transmitting infection between dogs [Dye, 1996; Gomez et al, 2018]. We modified the force of infection (FOI) to include a spatial dependence on a dispersal kernel function between infectious and susceptible dogs (Supplementary Information).…”
Section: Methodsmentioning
confidence: 99%
“…Mathematical models have suggested that canine vaccination could have a limited to no effect on the infection incidence in humans, as compared with insecticideimpregnated collars (Sevá et al, 2016;Shimozako et al, 2017;Gomez et al, 2018).…”
Section: Can Currently Licensed Canl Vaccines Reduce the Risk Of Infementioning
confidence: 99%